1993
DOI: 10.1037/0096-3445.122.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to extinction of fear-relevant stimuli: Preparedness or selective sensitization?

Abstract: Human conditioning research has revealed an apparent resistance to extinction of aversive conditioning to pictures of fear-relevant stimuli such as snakes and spiders, supporting M. E. P. Seligman's (1971) preparedness theory of fears and phobias. This article examines an alternative account based on activation of preexisting response tendencies under threat (selective sensitization). Two experiments demonstrate that selective sensitization of electrodermal responses is attenuated when a fear-relevant stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 42 publications
4
46
0
2
Order By: Relevance
“…This bias is translated into stronger conditioned reactions on other measures, such as SCRs (Davey, 1992;Lovibond, Siddle, & Bond, 1993). In our Experiment 2, selective learning effects were obtained on US expectancy ratings, replicating the US expectancy bias effect of Davey (1992) and Lovibond et al (1993).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This bias is translated into stronger conditioned reactions on other measures, such as SCRs (Davey, 1992;Lovibond, Siddle, & Bond, 1993). In our Experiment 2, selective learning effects were obtained on US expectancy ratings, replicating the US expectancy bias effect of Davey (1992) and Lovibond et al (1993).…”
Section: Discussionsupporting
confidence: 75%
“…This bias is translated into stronger conditioned reactions on other measures, such as SCRs (Davey, 1992;Lovibond, Siddle, & Bond, 1993). In our Experiment 2, selective learning effects were obtained on US expectancy ratings, replicating the US expectancy bias effect of Davey (1992) and Lovibond et al (1993). Arguably, the noreinforcement instructions rapidly abolished the expectancy bias for the fear-relevant CSwhereas the threat instructions retained the expectancy bias for the fear-relevant CS+2, resulting in a selective learning effect on US expectancy ratings.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The second is that context conditioning has cuespecific effects. Both possibilities suppose that pre-wired circuitry supports the processing of "fear-relevant" stimuli and that this circuitry becomes enabled under conditions of high fear, anxiety or arousal (Gray, 1982;1987;Lovibond et al, 1993). One study of humans found that an aversive electrical stimulation sensitized responding to "fear-relevant" stimuli but not to "fear-irrelevant" stimuli (Öhman et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It is even more rare to use the kind of compound test procedure employed here to evaluate the possibility of initial differences in fear. Indeed, the only study of which I am aware that has used such a test (Lovibond, Siddle, & Bond, 1993) was able to detect no differences attributable to the pairing of a fear-related CS with a shock, compared with the pairing of a fear-unrelated CS with a shock. That result is consistent with the possibility that observed differences reflect preexperimental differences in fear rather than differences that develop as a result of the associative conditioning conducted in the experiment.…”
Section: Discussionmentioning
confidence: 99%